Two-Year Functional Outcomes of Operative vs Nonoperative Treatment of Completely Displaced Midshaft Clavicle Fractures in Adolescents: Results From the Prospective Multicenter FACTS Study Group. Issue 11 (September 2022) - Heyworth, Benton E.; Pennock, Andrew T.; Li, Ying; Liotta, Elizabeth S.; Dragonetti, Brittany; Williams, David; Ellis, Henry B.; Nepple, Jeffrey J.; Spence, David; Willimon, S. Clifton; Perkins, Crystal A.; Pandya, Nirav K.; et al.
Background: The optimal treatment of midshaft clavicle fractures is controversial. Few previous comparative functional outcome studies have investigated these fractures in adolescents, the most commonly affected epidemiologic subpopulation. Purpose/Hypothesis: The purpose was to prospectively compare the outcomes of operative versus nonoperative treatment in adolescents with completely displaced midshaft clavicle fractures. The study hypothesis was that surgery would yield superior outcomes. Study Design: Cohort study; Level of evidence, 2. Methods: Patients aged 10 to 18 years treated for a midshaft clavicle fracture over a 5-year period at 1 of 8 pediatric centers were prospectively screened, with independent treatment decisions determined by individual musculoskeletal professionals. Demographics, radiographic clinical features, complications, and patient-reported outcomes (PROs) were prospectively recorded for 2 years. Regression and matching techniques were utilized to adjust for potential age- and fracture severity–based confounders for creation of comparable subgroups for analysis. Results: Of 416 adolescents with completely displaced midshaft clavicle fractures, 282 (68) provided 2-year PRO data. Operative patients (n = 88; 31%) demonstrated no difference in sex (78% male) or athletic participation but were older (mean age, 15.2 vs 13.5 years; P < .001), had more comminuted fractures (49.4% vs 26.3%; P < .001), and had greater fracture shortening (25.5 vs 20.7 mm; P < .001) than nonoperative patients (n = 194; 69%). There was no difference in mean PRO scores or rates of "suboptimal" scores (based on threshold values established a priori) between the operative and nonoperative treatment groups (American Shoulder and Elbow Surgeons, 96.8 vs 98.4; shortened version of the Disabilities of the Arm, Shoulder and Hand, 3.0 vs 1.6; EuroQol [EQ] visual analog scale, 93.0 vs 93.9; EQ–5 Dimensions index, 0.96 vs 0.98), even after regression and matching techniques adjusted for confounders. Operative patients had more unexpected subsequent surgery (10.4% vs 1.4%; P = .004) and clinically significant complications (20.8% vs 5.2%; P = .001). Overall, nonunion (0.4%), delayed union (1.9%), symptomatic malunion (0.4%), and refracture (2.6%) were exceedingly rare, with no difference between treatment groups. Conclusion: Surgery demonstrated no benefit in patient-reported quality of life, satisfaction, shoulder-specific function, or prevention of complications after completely displaced clavicle shaft fractures in adolescents at 2 years after injury. Registration: NCT04250415 (ClinicalTrials.gov identifier).